Determination the Key Success Factor for the Success Implementation and Long-Term Sustainability of Vendor Managed Inventory (VMI) - Cheong Shy Huoy; Suzari Abdul Rahim; Nor Aida Abdul Rahman; Mohd Nasrun Mohd Nawi; Aidi Ahmi (International Journal of Supply Chain Management, 2018)
The purpose of this study is to understand the key success factor for success implementation and long-term sustainability of Vendor Managed Inventory (VMI). The respondents for this study was employees who work in supply chain related department in electronic and electrical industry in Malaysia. The independent variables include integrated system and common platform, relationship quality and commitment, information quality and clearly outline expectation and communication. While the identified dependent variable is the key success factor for VMI implementation and sustainability. The management commitment is regarded as moderating effect of the relationship between independent and dependent variables. The data is collected using online questionnaire and subsequently analysed using SPSS and PLS. The relationship of variables is tested and examined. The finding demonstrates quality of information have positive and significant relationship with long term sustainability and success implementation of VMI. Besides, the study gives implication that there is positive relationship between relationship quality and integrated system toward VMI sustainability but they do not have significant influence against VMI implementation and sustainability. While expectation have negative and insignificant influence towards VMI implementation. The moderator effect of management commitment been assessed as insignificant as well.